Analysis the Difficulty of Indonesian Language Class V Elementary School / Analisis Tingkat Kesulitan Bahasa Indonesia Kelas V Madrasah Ibtidaiyah - Ruhil Ruhil (STAI Ma'had Aly Al-Hikam Malang, 2020)
Indonesian Language subject is often considered easy by studensts, students are able to answer questions even though they don’t study it, and get the highest score compared to other subjects. This study aims to explain the level of difficulty and cognitive level of question of Bahasa Indonesia subject in Class V MIN 2 Banda Aceh. The question were given in the examination of odd semester 2019. The type of this research is quantitative descriptive by examining the relationship between one variable with another variable. Data collection techniques to get more detailed information wasgained by interviewing Teacher of Bahasa Indonesia Subject of Class V MIN 2 Banda Aceh. Object of this study was question sheet of Bahasa Indonesia in semester 2019, and student answers. The results showed that the difficulty level of the questions was 25% in the easy category, 65% the medium category, and 10% in the difficult categories. On the other hand, the cognitive level of questions is87.5% in the categories C1, 5% in the categories C2 questions and 7.75% in the categories C6 questions while C3, C4, and C5 categories are not found.